Neonatal screening for severe combined immunodeficiency in Brazil - Marilia Pyles Patto Kanegae; Lucila Akune Barreiros; Juliana Themudo Lessa Mazzucchelli; Sonia Marchezi Hadachi; Laura Maria de Figueiredo Ferreira Guilhoto; Ana Lúcia Acquesta; Isabel Rugue Genov; Silvia Maia Holanda; Regina Sumiko Watanabe Di Gesu; Ana Lucia Goulart; Amélia Miyashiro Nunes dos Santos; Newton Bellesi; et al. (Brazilian Society of Pediatrics, 2016)
Objective: To apply, in Brazil, the T‐cell receptor excision circles (TRECs) quantification technique using real‐time PCR in newborn screening for severe combined immunodeficiency (SCID) and assess the feasibility of implementing it on a large scale in Brazil. Methods: 8715 newborn blood samples were collected on paper filter and, after DNA elution, TRECs were quantified by real‐time PCR. The cutoff value to determine whether a sample was abnormal was determined by ROC curve analysis, using SSPS. Results: The concentration of TRECs in 8682 samples ranged from 2 to 2181 TRECs/μL of blood, with mean and median of 324 and 259 TRECs/μL, respectively. Forty‐nine (0.56%) samples were below the cutoff (30 TRECs/μL) and were reanalyzed. Four (0.05%) samples had abnormal results (between 16 and 29 TRECs/μL). Samples from patients previously identified as having SCID or DiGeorge syndrome were used to validate the assay and all of them showed TRECs below the cutoff. Preterm infants had lower levels of TRECs than full‐term neonates. The ROC curve showed a cutoff of 26 TRECs/μL, with 100% sensitivity for detecting SCID. Using this value, retest and referral rates were 0.43% (37 samples) and 0.03% (3 samples), respectively. Conclusion: The technique is reliable and can be applied on a large scale after the training of technical teams throughout Brazil